The Effect Of Health Education In Prevention Hypertension Of Patient Knowledge In Tolo’ Public Health Center Jeneponto District - Imelda Appulembang; Musaidah Musaidah; Sri Wahyuni Bahrum; Jumrah Riani (International Journal of Health and Pharmaceutical (IJHP), 2022)
Hypertension can increase the risk of death and complications. Health education is carried out with the aim of increasing health knowledge while increasing public awareness of the importance of maintaining health. It is known that there is an effect of health education in preventing hypertension on the knowledge of patients at the Tolo' Public Health Center, Jeneponto Regency. The type of research used is quantitative with a descriptive research design using a cross sectional approach. To determine the relationship between the independent variable and the dependent variable by using joint measurements, the total population is 170 people, the sampling of this study used purposive sampling technique so that the results were 32 respondents, the data measurement instrument used a questionnaire. There is an effect of health education in preventing hypertension on knowledge of patients and there is an influence of knowledge in preventing hypertension on knowledge of patients at the Tolo' Public Health Center, Jeneponto Regency. obtained p-Value = 0.000 (α<0.05). There is an effect of health education and knowledge in preventing hypertension on knowledge of patients at the Tolo' Public Health Center, Jeneponto Regency.